Are training programs more effective when unemployment is high? - Michael Lechner; Conny Wunsch (Institute for the Study of Labor (IZA), 2006)
We estimate short, medium, and long-run individual labor market effects of training programs for unemployed by following program participation on a monthly basis over a ten-year period. Since analyzing the effectiveness of training over such a long period is impossible with experimental data, we use an administrative database compiled for evaluating German training programs. Based on matching estimation adapted to the various issues that arise in this particular context, we find a clear positive relation between the effectiveness of the programs and the unemployment rate over time.
urn:nbn:de:101:1-20090622332
Keywords: 330; Arbeitsmarktpolitik; Berufliche Integration; Weiterbildung; Beschäftigungseffekt; Arbeitslosigkeit; Wirkungsanalyse; Deutschland